Biocidal activity of Ziziphora hispanica L and Satureja calamintha Scheele L essential oils against the Callosobruchus maculatus (Fabricius) pest on cowpea seeds during storage - Baghouz, Asmae; Bouchelta, Yassir; Es-safi, Imane; El Brahimi, Rajae; Imtara, Hamada; AlZain, Mashail N.; Noman, Omer M.; Shahat, Abdelaaty A.; Guemmouh, Raja (Frontiers in Sustainable Food Systems, 2024)
The goal of the current study is to identify environmentally appropriate substitutes for synthetic pesticides in the management of stored seed pests. Thus, in a laboratory setting, the insecticidal activity of essential oils (EOs) from Ziziphora hispanica and Satureja calamintha against the cowpea weevil C. maculatus was assessed. The fumigant effects of these two EOs were tested on four biological parameters of C. maculatus: adult mortality, fecundity, female fertility, and adult emergence, while concentrations of 4, 12, 16, and 20 μL/cm 2 of air were used for the repulsion test. The results of fumigation tests showed a remarkable efficacy of both essential oils against adult C. maculatus after 24 hours of exposure. Z. hispanica EO yielded a mortality rate of 80 ± 20%, with an LC50 of 2.77 μL L -1 for males and 66.66 ± 11.54% with an LC50 of 3.57 μL L-1 for females at 4 μL L -1 of air. However, the S. calamintha EO resulted in a mortality rate of 100% for males and 86.66 ± 23.09% with an LC50 of 2.17 μL L -1 for females at low doses. The fecundity was 1.33 ± 0.57 eggs per female. In contrast, this parameter was absent with S. calamintha EO at the low dose, while fertility and emerging adults were missing for both EOs. Furthermore, both EOs showed highly repellent activity towards C. maculatus adults, with 81.66% for Z. hispanica and 91.67% for S. calamintha EO. According to the results of the GC-MS analysis, the primary components of Z. hispanica EO were found to be pulegone (28.17%), alpha-naphtonitrite (10.77%), and 3-(3-thienyl) pro-2-enoic acid (10.62%). Similarly, the main constituents of S. calamintha EO were pulegone (21.48%), piperitenone oxide (17.71%), and eucalyptol (11.99%). Hence, these substances are regarded as the volatile compounds accountable for controlling C. maculatus activities. The study reports that Z. hispanica and S. calamintha show promising fumigant and repellent efficacy and offer new avenues for their potential use as an alternative to synthetic pesticides against stored seed pests.